Prognostic potential of circulatory miR-19a-3p, miR-19b-3p, and miR-329–3p for future hypertension diagnosis - Kostiniuk, Daria; Blankenstein, Antti; Rajić, Sonja; Ciantar, Joanna; Mononen, Nina; Lyytikäinen, Leo-Pekka; Seppälä, Ilkka; Mishra, Pashupati P.; Juonala, Markus; Waldenberger, Melanie; Elovainio, Marko; Oksala, Niku; et al. (Lippincott, 2026)
MicroRNAs have been suggested as essential hypertension biomarkers, but evidence remains inconclusive due to limited high-throughput studies in population cohorts.
We analyzed data from the Young Finns Study (YFS) from 2011 and 2018–2020 to assess cross-sectional and prospective associations between circulatory microRNAs, blood pressure (BP), and hypertension. Hypertension risk prediction potential was assessed using nested logistic and Weibull survival models; model performance was evaluated with likelihood ratio (LR) test and c-statistic. All models were adjusted with relevant risk factors.
In 2011, whole blood microRNAs were profiled for 871 individuals (83 with hypertension); in 2018–2020, 760 were re-examined, with 67 newly diagnosed. Cross-sectionally, 16 miRNAs correlated with BP (Spearman, PFDR < 0.05); miR-122–5p (fold change = 1.33) and miR-144–5p (fold change = -1.10) differentiated hypertensive individuals (U test, PFDR < 0.05). Associations persisted in adjusted regression models and some replicated in LURIC (n = 999) and YFS serum data (n = 126). Prospectively, miR-19a-3p [odds ratio (OR) = 1.51, 95% confidence interval (95% CI): 1.14–2.18], miR-19b-3p (OR = 1.50, 95% CI:1.11–2.04), and miR-329–3p (OR = 0.58, 95% CI: 0.39–0.74) levels prognosed hypertension incident. miR-329–3p improved model fit (LR test, P = 2.85×10–4) and discrimination (c-statistic = 0.849, Δ = 0.026). miR-19b-3p predicted time to onset (hazard ratio = 2.13, 95% CI: 1.38–4.45), improving model fit (LR test, P = 0.0012) and time-dependent discrimination at 7 and 8-year horizons.
Our findings highlight both novel and previously reported miRNAs associating with BP and hypertension and suggest that miR-329–3p, miR-19a-3p, and miR-19b-3p as promising candidates for further investigation in hypertension risk prediction.